New tools target oil quality sweetspots in viscous oil accumulations - Smalley,PC; Goodwin,NS; Dillon,JF; Bidinger,CR; Drozd,RJ (1996)
API gravity and dead oil viscosity can be predicted using geochemical parameters measured from core or sidewall core samples. Spatial variations in oil properties can be difficult to map empirically simply by contouring data, since more than one controlling factor may be operative. A major step in improving fluid mapping is to identify and quantify these controls and map them. These maps are then used to attempt oil sweetspot prediction in areas away from well control.